The employment of advanced fiber laser technology to weld dissimilar materials: Stainless steel and aluminum alloy using pre-placed powder-based activating flux and filler - Ezazi, M.A. (2015)
The dissimilar materials welding was carried out between austenitic stainless steel 304 L (low carbon) and aluminum alloy 5083 by a low power single-mode continuous wave Ytterbium fiber laser in steel-on-aluminum overlapping configuration and keyhole mode. In order to compensate for both the mechanical properties and appearance deficiencies such as: underfilling, spattering, solidification cracks, excessive formation of Fe-Al intermetallic compounds in addition to lack of sufficient shear strength, various combinations of pre-placed powder-based activating fluxes including oxide- based TiO2 (titanium dioxide) and halide-based CaF2 (calcium fluoride) powders in addition to the mixture of pure iron-aluminum powder filler were utilized in order to investigate their effects on the metallurgical and mechanical properties of the joints. To characterize the joints, shear tests were carried out in order to identify the influence of laser welding parameters and powders on welded joints' strength. The elemental composition, crystallographic characteristics in addition to failure mechanism of the welded joints were evaluated using Energy-dispersive spectroscopy (EDX) and X-ray diffraction (XRD) respectively, beside that the Vickers microhardness was employed in order to identify the location of various FexAly intermetallic compound phases across the fusion, heat affected and unaffected zones. Furthermore, the microstructure and morphology of the weld fillets were characterized using Field emission scanning electron (FESEM) and Optical microscopes. The obtained results show that, the application of oxide and halide activating fluxes led to remarkable decrease in welding defects including the hot cracks, pores and inclusions which resulted in tensile properties improvement up to 1.66 and 2.14 times in average respectively compared with autogenous joints welded without any powder. The enhancement in mechanical properties and appearance of the joints is related to special mechanism of activating fluxes through which the laser plasma can be formed in a shorter period of time leading to faster laser-material coupling, shorter thermal history and better heat conduction throughout the whole thickness of welding materials, which can promote the uniform heat distribution leading to an increase in penetration depth, decrease in surface depression and material ejection, restriction of intermetallic compounds and preservation of hardness across the weld nuggets. Moreover, the enhanced convection after usage of activating fluxes led to better molten pool circulation which resulted in constitution of joints with root-shape morphology possessing mechanical interlock characteristics. Correspondingly, the severe underfilling and spattering observed during the welding process as a result of alloying elements evaporation was eliminated completely after the application of pre-placed Fe-Al powder filler which led to significant enhancement in weldments' appearance and shear strength.